2021
DOI: 10.1002/jclp.23272
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal investigation of the meaning‐making model in midlife adults who have experienced trauma

Abstract: Introduction Park and Folkman's (1997) meaning‐making model posits that distress from traumatic events stems from discrepancies between one's global meaning framework and appraised situational meaning of the traumatic event, with meaning making diminishing these discrepancies and thus bolstering well‐being. The current study investigates this supposition over a 19‐year span in mid‐life adults. Methods We selected participants from the Midlife in the United States (MIDUS) study who had indicated the experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Severe trauma can disrupt a person’s global meaning ( Janoff-Bulman, 1989 ). Making meaning typically involves cognitive processing of appraised and global meanings to change or reframe them and make them more consistent ( Fitzke et al, 2021 ; Huang et al, 2021 ). People can change situational appraisals to better integrate them into their global meaning system (assimilation), such as coming to see the event as less damaging or, perhaps, even positive in its consequences ( Paquin et al, 2021 ; Park and Boals, 2021 ).…”
Section: Situational Meaningmentioning
confidence: 99%
See 3 more Smart Citations
“…Severe trauma can disrupt a person’s global meaning ( Janoff-Bulman, 1989 ). Making meaning typically involves cognitive processing of appraised and global meanings to change or reframe them and make them more consistent ( Fitzke et al, 2021 ; Huang et al, 2021 ). People can change situational appraisals to better integrate them into their global meaning system (assimilation), such as coming to see the event as less damaging or, perhaps, even positive in its consequences ( Paquin et al, 2021 ; Park and Boals, 2021 ).…”
Section: Situational Meaningmentioning
confidence: 99%
“…Positive reappraisal, looking for ways to view the situation in a more positive light, or focusing on identifying positive attributes of an event and reminding oneself of those benefits, are very common meaning-making strategies ( Park, 2010 ). A longitudinal study of a national sample of Americans (the Midlife in the United States Series Study) found that attempting to making meaning of a highly stressful or traumatic life event through positive reappraisal was associated with subsequent higher levels of positive mood and lower levels of negative mood years later ( Fitzke et al, 2021 ). Other meaning making strategies include seeking more benign explanations for the situation and making downward comparisons with real or hypothetical others in relatively poorer straits ( Gerber et al, 2018 ).…”
Section: Situational Meaningmentioning
confidence: 99%
See 2 more Smart Citations
“…As a dynamic process leading to changes in meaning in life, and other outcomes over time, meaning making is necessarily studied with repeated measures designs. Some research has employed longitudinal data to examine meaning making processes, assessing meaning-making strategies and meaning in life only a few times with measurements timepoints spaced apart widely, for instance three measurements spaced nine years apart each (Fitzke et al, 2021) or two measurements spaced one year apart (Park et al, 2008). While these research designs provide useful insights regarding the resulting outcomes of meaning making processes, the ESM could offer more finegrained information about shifts in meaning in life over the course of meaning making, rather than simply before and after snapshots, to foster a deeper understanding of these cognitive and emotional efforts as they unfold in real time.…”
Section: Accounting For Dynamic Meaning Processesmentioning
confidence: 99%